Advantages of Fluoroscopy for Accidental Ingestion of Multiple Magnets - Toshihiko Kakiuchi; Tetsuya Nosho (Case Reports in Pediatrics)
Foreign body ingestion is one of the common problems among children. A three-year-old girl presented to the emergency department 2 h after ingesting three small disk-type neodymium magnets. She had no gastrointestinal symptoms. Abdominal radiography revealed a foreign body in the left upper quadrant, which was the three circular magnets. Fluoroscopy was performed. She was placed in the right lateral decubitus position for 3 min and slowly returned to the supine position. Abdominal fluoroscopy revealed a foreign body migrating near the middle of the spine. Similarly, when she was placed in the left lateral decubitus position for 3 min and slowly returned to the supine position, the foreign body migrated to the outermost part of her left upper quadrant. Thus, we anticipated that the magnets could be excreted spontaneously. The patient did not develop any gastrointestinal symptoms after returning home, and two days later, three overlapping magnets were finally found in her stool. During accidental ingestion of single or multiple desk-type neodymium magnets, endoscopic removal may not be necessary if they are mobile and clump together in the stomach. Regarding the ingestion of multiple desk-type neodymium magnets, fluoroscopy is useful to determine the extent of endoscopic intervention.